A new tool to derive chemical abundances in type-2 active galactic nuclei. Issue Volume 15:Issue S356(2019) (October 2019) - García-Benito, Rubén; Pérez-Montero, Enrique; Dors, Oli L.; Vlchez, José M.; Cardaci, Monica V.; Hägele, Guillermo F.
Abstarct: We present a new tool for the analysis of the optical emission lines of the gas in the Narrow Line Region (NLR) around Active Galactic Nuclei (AGNs). This new tool can be used in large samples of objects in a consistent way using different sets of optical emission-lines taking into the account possible variations from the O/H - N/O relation. The code compares certain observed emission-line ratios with the predictions from a large grid of photoionization models calculated under the most usual conditions in the NLR of AGNs to calculate the total oxygen abundance, nitrogen-to-oxygen ratio and ionization parameter. We applied our method to a sample of Seyfert 2 galaxies with optical emission-line fluxes from the literature. Our results confirm the high metallicity of the objects of the sample and provide consistent values with the direct method. The usage of models to calculate precise ICFs is mandatory when only optical emission lines are available to derive chemical abundances using the direct method in NLRs of AGN.